Local Politics Meets Chinese Engineers: A Study of the Chinese-Built Standard Gauge Railway Project in Kenya - Uwe Wissenbach; Yuan Wang (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2016)
As part of China's new "Belt and Road Initiative," Kenya's Standard Gauge Railway (SGR) aims to open East and Central Africa up to Chinese trade and investment. The first phase of the SGR, from Mombassa to Nairobi, is being constructed by the China Roads and Bridges Corporation (CRBC). Much like other Chinese infrastructure projects in Africa, the SGR has sparked controversy around its economic viability, opaque contracting practices, financing arrangements, and community and labor issues. Yet, as this policy brief by Uwe Wissenbach and Yuan Wang shows, the project has also created modest development opportunities for local content, jobs, and skills.
Keywords: 330